Role of probiotics VSL#3 in prevention of suspected sepsis in low birthweight infants in India: a randomised controlled trial. Issue 7 (10th July 2015) - Sinha, Anju; Gupta, Subodh S; Chellani, Harish; Maliye, Chetna; Kumari, Vidya; Arya, Sugandha; Garg, BS; Gaur, Sunita Dixit; Gaind, Rajni; Deotale, Vijayshri; Taywade, Manish; Prasad, MS; et al.
Abstract : Objectives: To assess the effect of the probiotic VSL#3 in prevention of neonatal sepsis in low birthweight (LBW) infants. Design: Randomised, double-blind, placebo-controlled trial. Setting: Community setting in rural India. Participants: LBW infants aged 3–7 days. Interventions: Infants were randomised to receive probiotic (VSL#3, 10 billion colony-forming units (cfu)) or placebo for 30 days, and were followed up for 2 months. Main outcome measure: Possible serious bacterial infection (PSBI) as per the Integrated Management of Neonatal Childhood Illnesses algorithm, as diagnosed by fieldworkers/physicians. Results: 668 infants were randomised to VSL#3 and 672 to placebo. By intention-to-treat analysis, the risk of PSBI among infants in the overall population of LBW infants was not statistically significant (RR 0.79 (95% CI 0.56 to 1.03)). Probiotics reduced median days of hospitalisation (6 days vs 3 days in probiotics) (p=0.018) but not the risk of hospitalisation (RR 0.66 (95% CI 0.42 to 1.04). The onset of PSBI in 10% of infants occurred on the 40th day in the probiotics arm versus the 25th day in the control arm (p=0.063). Conclusions: Daily supplementation of LBW infants with probiotics VSL#3 (10 billion cfu) for 30 days led to a non-significant 21% reduction in risk of neonatal sepsis. A larger study with sufficient power and a more specific primary end point is warranted to confirm the preventive effect of VSL#3 on neonatal sepsis in LBW infants. Trial registration number: The study is registered at the Clinical Trial Registry of India (CTRI/2008/091/000049).